Pengaruh Promosi Berbasis Sosial Media Terhadap Niat Beli Produk Jasa pada Lembaga Pelatihan Kerja Technico Lampung - Muhammad Lungit Wicaksono; Driya Wiryawan; Dwi Asri Siti Ambarwati; Rinaldi Bursan (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
Promotion is an element of the marketing mix that focuses on efforts to inform, persuade, and remind consumers of the company's brands and products. This study aims to determine the effect of social media-based promotions, namely entertainment, interaction, and trends on the purchase intention of service products at the Technico Lampung Job Training Institute. The Technico Lampung Job Training Institute has entertainment that can make consumers comfortable on the Facebook page which affects consumers' purchase intentions, Interaction affects consumers' purchase intentions, the implications of accepting this hypothesis are that the Technico Job Training Institute needs to be more active in replying to comments, replying to messages of criticism and suggestions. Log in to the Technico Job Training Institute facebook page, Trends affect consumers' purchase intentions. The implication of accepting this hypothesis is that the Technico Job Training Institute needs to pay attention to the current trend movements before making posts on the Facebook page and ultimately affecting consumers' purchase intentions